"I Can Understand Where They're Coming From": How Clinicians' Disability Experiences Shape Their Interaction With Clients. (November 2020) - Battalova, Alfiya; Bulk, Laura; Nimmon, Laura; Hole, Rachelle; Krupa, Terry; Lee, Michael; Mayer, Yael; Jarus, Tal
Students and clinicians with disabilities are underrepresented in the academic health programs and professional clinical settings. Disability studies foregrounds the unique ways of knowing and being that clinicians with disabilities can offer. Based on a larger grounded theory study of the experiences of students and clinicians with disabilities, this article examines the role that clinicians' abilities to draw on their personal experiences of living with a disability have on their interactions with clients. The analysis of semistructured interviews with 55 students and clinicians with disabilities from different fields contributes to the development of a theory of epistemic connection. The theory is informed by the following three themes: (a) building rapport through understanding, (b) from understanding to advocacy and creative approaches, and (c) between professionalism and disability . The findings emphasize not only the importance of diversifying the health care workforce but also incorporating disability epistemology into the health care culture.